Sequencing-Based Measurable Residual Disease Testing in Acute Myeloid Leukemia - Yoest, Jennifer M.; Shirai, Cara Lunn; Duncavage, Eric J. (Frontiers in Cell and Developmental Biology, 2020)
Next generation sequencing (NGS) methods have allowed for unprecedented genomic characterization of acute myeloid leukemia (AML) over the last several years. Further advances in NGS based methods including error correction using unique molecular identifiers (UMIs) have more recently enabled the use of NGS-based measurable residual disease (MRD) detection. This review focuses on the use of NGS-based MRD detection in AML, including basic methodologies and clinical applications.